Pengembangan Media Scrapbook untuk Meningkatkan Minat Belajar Pendidikan Pancasila di SMA Negeri 1 Rantau Utara - Berliana Sinurat; Englin Sianturi; Yuli Ida Arta Simatupang (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to develop a learning medium in the form of a scrapbook as an effort to increase students’ interest in learning Pancasila Education at SMAN 1 Rantau Utara. The main problem addressed is the low level of student interest in theoretical subjects, which are often perceived as less engaging. This research employs a Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The subjects of this study were eleventh-grade students at SMAN 1 Rantau Utara. The feasibility test results from material and media experts indicated that the scrapbook media falls into the